Effects of the demographic characteristics and physical exercises on elementary school teacher’s job satisfaction - Shariff, Asma Ahmad (Shaheed Benazir Bhutto Women Univ., Pakistan, 2021)
The objective of this study was to examine the effect of demographic characteristics and physical exercise on elementary school teacher’s job satisfaction. A survey design was used in the current study. The sample consisted of 186 elementary school teachers from two towns of District Lahore. Statistical Package for the Social Sciences was used to analyze the data in the form of frequency, standard deviation, and percentages. The findings indicated that gender has no effect on elementary teachers’ job satisfaction. The qualification of teachers was not significantly associated with teachers’ job satisfaction. The experience effected teacher’s job satisfaction. The physical exercises were significantly associated with teachers’ job satisfaction. It was concluded from the findings that gender and subject of teaching had no effect on elementary teachers’ job satisfaction. It was recommended that elementary school teacher’s physical exercise sessions be given due consideration in the school induction as it showed an association with teachers’ job satisfaction. © 2021, Shaheed Benazir Bhutto Women University. All rights reserved.